431
|
1 {-# OPTIONS --allow-unsolved-metas #-}
|
|
2 open import Level
|
|
3 open import Ordinals
|
|
4 module ODUtil {n : Level } (O : Ordinals {n} ) where
|
|
5
|
|
6 open import zf
|
|
7 open import Data.Nat renaming ( zero to Zero ; suc to Suc ; ℕ to Nat ; _⊔_ to _n⊔_ )
|
|
8 open import Relation.Binary.PropositionalEquality hiding ( [_] )
|
|
9 open import Data.Nat.Properties
|
|
10 open import Data.Empty
|
|
11 open import Relation.Nullary
|
|
12 open import Relation.Binary hiding ( _⇔_ )
|
|
13
|
|
14 open import logic
|
|
15 open import nat
|
|
16
|
|
17 open Ordinals.Ordinals O
|
|
18 open Ordinals.IsOrdinals isOrdinal
|
|
19 open Ordinals.IsNext isNext
|
|
20 import OrdUtil
|
|
21 open OrdUtil O
|
|
22
|
|
23 import OD
|
|
24 open OD O
|
|
25 open OD.OD
|
|
26 open ODAxiom odAxiom
|
|
27
|
|
28 open HOD
|
|
29 open _⊆_
|
|
30 open _∧_
|
|
31 open _==_
|
|
32
|
|
33 cseq : HOD → HOD
|
|
34 cseq x = record { od = record { def = λ y → odef x (osuc y) } ; odmax = osuc (odmax x) ; <odmax = lemma } where
|
|
35 lemma : {y : Ordinal} → def (od x) (osuc y) → y o< osuc (odmax x)
|
|
36 lemma {y} lt = ordtrans <-osuc (ordtrans (<odmax x lt) <-osuc )
|
|
37
|
|
38
|
|
39 pair-xx<xy : {x y : HOD} → & (x , x) o< osuc (& (x , y) )
|
|
40 pair-xx<xy {x} {y} = ⊆→o≤ lemma where
|
|
41 lemma : {z : Ordinal} → def (od (x , x)) z → def (od (x , y)) z
|
|
42 lemma {z} (case1 refl) = case1 refl
|
|
43 lemma {z} (case2 refl) = case1 refl
|
|
44
|
|
45 pair-<xy : {x y : HOD} → {n : Ordinal} → & x o< next n → & y o< next n → & (x , y) o< next n
|
|
46 pair-<xy {x} {y} {o} x<nn y<nn with trio< (& x) (& y) | inspect (omax (& x)) (& y)
|
|
47 ... | tri< a ¬b ¬c | record { eq = eq1 } = next< (subst (λ k → k o< next o ) (sym eq1) (osuc<nx y<nn)) ho<
|
|
48 ... | tri> ¬a ¬b c | record { eq = eq1 } = next< (subst (λ k → k o< next o ) (sym eq1) (osuc<nx x<nn)) ho<
|
|
49 ... | tri≈ ¬a b ¬c | record { eq = eq1 } = next< (subst (λ k → k o< next o ) (omax≡ _ _ b) (subst (λ k → osuc k o< next o) b (osuc<nx x<nn))) ho<
|
|
50
|
|
51 -- another form of infinite
|
|
52 -- pair-ord< : {x : Ordinal } → Set n
|
|
53 pair-ord< : {x : HOD } → ( {y : HOD } → & y o< next (odmax y) ) → & ( x , x ) o< next (& x)
|
|
54 pair-ord< {x} ho< = subst (λ k → & (x , x) o< k ) lemmab0 lemmab1 where
|
|
55 lemmab0 : next (odmax (x , x)) ≡ next (& x)
|
|
56 lemmab0 = trans (cong (λ k → next k) (omxx _)) (sym nexto≡)
|
|
57 lemmab1 : & (x , x) o< next ( odmax (x , x))
|
|
58 lemmab1 = ho<
|
|
59
|
|
60 trans-⊆ : { A B C : HOD} → A ⊆ B → B ⊆ C → A ⊆ C
|
|
61 trans-⊆ A⊆B B⊆C = record { incl = λ x → incl B⊆C (incl A⊆B x) }
|
|
62
|
|
63 refl-⊆ : {A : HOD} → A ⊆ A
|
|
64 refl-⊆ {A} = record { incl = λ x → x }
|
|
65
|
|
66 od⊆→o≤ : {x y : HOD } → x ⊆ y → & x o< osuc (& y)
|
|
67 od⊆→o≤ {x} {y} lt = ⊆→o≤ {x} {y} (λ {z} x>z → subst (λ k → def (od y) k ) &iso (incl lt (d→∋ x x>z)))
|
|
68
|
|
69 subset-lemma : {A x : HOD } → ( {y : HOD } → x ∋ y → (A ∩ x ) ∋ y ) ⇔ ( x ⊆ A )
|
|
70 subset-lemma {A} {x} = record {
|
|
71 proj1 = λ lt → record { incl = λ x∋z → proj1 (lt x∋z) }
|
|
72 ; proj2 = λ x⊆A lt → ⟪ incl x⊆A lt , lt ⟫
|
|
73 }
|
|
74
|
|
75
|
|
76 ω<next-o∅ : {y : Ordinal} → infinite-d y → y o< next o∅
|
|
77 ω<next-o∅ {y} lt = <odmax infinite lt
|
|
78
|
|
79 nat→ω : Nat → HOD
|
|
80 nat→ω Zero = od∅
|
|
81 nat→ω (Suc y) = Union (nat→ω y , (nat→ω y , nat→ω y))
|
|
82
|
|
83 ω→nato : {y : Ordinal} → infinite-d y → Nat
|
|
84 ω→nato iφ = Zero
|
|
85 ω→nato (isuc lt) = Suc (ω→nato lt)
|
|
86
|
|
87 ω→nat : (n : HOD) → infinite ∋ n → Nat
|
|
88 ω→nat n = ω→nato
|
|
89
|
|
90 ω∋nat→ω : {n : Nat} → def (od infinite) (& (nat→ω n))
|
|
91 ω∋nat→ω {Zero} = subst (λ k → def (od infinite) k) (sym ord-od∅) iφ
|
|
92 ω∋nat→ω {Suc n} = subst (λ k → def (od infinite) k) lemma (isuc ( ω∋nat→ω {n})) where
|
|
93 lemma : & (Union (* (& (nat→ω n)) , (* (& (nat→ω n)) , * (& (nat→ω n))))) ≡ & (nat→ω (Suc n))
|
|
94 lemma = subst (λ k → & (Union (k , ( k , k ))) ≡ & (nat→ω (Suc n))) (sym *iso) refl
|
|
95
|
|
96 pair1 : { x y : HOD } → (x , y ) ∋ x
|
|
97 pair1 = case1 refl
|
|
98
|
|
99 pair2 : { x y : HOD } → (x , y ) ∋ y
|
|
100 pair2 = case2 refl
|
|
101
|
|
102 single : {x y : HOD } → (x , x ) ∋ y → x ≡ y
|
|
103 single (case1 eq) = ==→o≡ ( ord→== (sym eq) )
|
|
104 single (case2 eq) = ==→o≡ ( ord→== (sym eq) )
|
|
105
|
|
106 open import Relation.Binary.HeterogeneousEquality as HE using (_≅_ )
|
|
107 -- postulate f-extensionality : { n m : Level} → HE.Extensionality n m
|
|
108
|
|
109 ω-prev-eq1 : {x y : Ordinal} → & (Union (* y , (* y , * y))) ≡ & (Union (* x , (* x , * x))) → ¬ (x o< y)
|
|
110 ω-prev-eq1 {x} {y} eq x<y = eq→ (ord→== eq) {& (* y)} (λ not2 → not2 (& (* y , * y))
|
|
111 ⟪ case2 refl , subst (λ k → odef k (& (* y))) (sym *iso) (case1 refl)⟫ ) (λ u → lemma u ) where
|
|
112 lemma : (u : Ordinal) → ¬ def (od (* x , (* x , * x))) u ∧ def (od (* u)) (& (* y))
|
|
113 lemma u t with proj1 t
|
|
114 lemma u t | case1 u=x = o<> (c<→o< {* y} {* u} (proj2 t)) (subst₂ (λ j k → j o< k )
|
|
115 (trans (sym &iso) (trans (sym u=x) (sym &iso)) ) (sym &iso) x<y ) -- x ≡ & (* u)
|
|
116 lemma u t | case2 u=xx = o<¬≡ (lemma1 (subst (λ k → odef k (& (* y)) ) (trans (cong (λ k → * k ) u=xx) *iso ) (proj2 t))) x<y where
|
|
117 lemma1 : {x y : Ordinal } → (* x , * x ) ∋ * y → x ≡ y -- y = x ∈ ( x , x ) = u
|
|
118 lemma1 (case1 eq) = subst₂ (λ j k → j ≡ k ) &iso &iso (sym eq)
|
|
119 lemma1 (case2 eq) = subst₂ (λ j k → j ≡ k ) &iso &iso (sym eq)
|
|
120
|
|
121 ω-prev-eq : {x y : Ordinal} → & (Union (* y , (* y , * y))) ≡ & (Union (* x , (* x , * x))) → x ≡ y
|
|
122 ω-prev-eq {x} {y} eq with trio< x y
|
|
123 ω-prev-eq {x} {y} eq | tri< a ¬b ¬c = ⊥-elim (ω-prev-eq1 eq a)
|
|
124 ω-prev-eq {x} {y} eq | tri≈ ¬a b ¬c = b
|
|
125 ω-prev-eq {x} {y} eq | tri> ¬a ¬b c = ⊥-elim (ω-prev-eq1 (sym eq) c)
|
|
126
|
|
127 ω-∈s : (x : HOD) → Union ( x , (x , x)) ∋ x
|
|
128 ω-∈s x not = not (& (x , x)) ⟪ case2 refl , subst (λ k → odef k (& x) ) (sym *iso) (case1 refl) ⟫
|
|
129
|
|
130 ωs≠0 : (x : HOD) → ¬ ( Union ( x , (x , x)) ≡ od∅ )
|
|
131 ωs≠0 y eq = ⊥-elim ( ¬x<0 (subst (λ k → & y o< k ) ord-od∅ (c<→o< (subst (λ k → odef k (& y )) eq (ω-∈s y) ))) )
|
|
132
|
|
133 nat→ω-iso : {i : HOD} → (lt : infinite ∋ i ) → nat→ω ( ω→nat i lt ) ≡ i
|
|
134 nat→ω-iso {i} = ε-induction {λ i → (lt : infinite ∋ i ) → nat→ω ( ω→nat i lt ) ≡ i } ind i where
|
|
135 ind : {x : HOD} → ({y : HOD} → x ∋ y → (lt : infinite ∋ y) → nat→ω (ω→nat y lt) ≡ y) →
|
|
136 (lt : infinite ∋ x) → nat→ω (ω→nat x lt) ≡ x
|
|
137 ind {x} prev lt = ind1 lt *iso where
|
|
138 ind1 : {ox : Ordinal } → (ltd : infinite-d ox ) → * ox ≡ x → nat→ω (ω→nato ltd) ≡ x
|
|
139 ind1 {o∅} iφ refl = sym o∅≡od∅
|
|
140 ind1 (isuc {x₁} ltd) ox=x = begin
|
|
141 nat→ω (ω→nato (isuc ltd) )
|
|
142 ≡⟨⟩
|
|
143 Union (nat→ω (ω→nato ltd) , (nat→ω (ω→nato ltd) , nat→ω (ω→nato ltd)))
|
|
144 ≡⟨ cong (λ k → Union (k , (k , k ))) lemma ⟩
|
|
145 Union (* x₁ , (* x₁ , * x₁))
|
|
146 ≡⟨ trans ( sym *iso) ox=x ⟩
|
|
147 x
|
|
148 ∎ where
|
|
149 open ≡-Reasoning
|
|
150 lemma0 : x ∋ * x₁
|
|
151 lemma0 = subst (λ k → odef k (& (* x₁))) (trans (sym *iso) ox=x) (λ not → not
|
|
152 (& (* x₁ , * x₁)) ⟪ pair2 , subst (λ k → odef k (& (* x₁))) (sym *iso) pair1 ⟫ )
|
|
153 lemma1 : infinite ∋ * x₁
|
|
154 lemma1 = subst (λ k → odef infinite k) (sym &iso) ltd
|
|
155 lemma3 : {x y : Ordinal} → (ltd : infinite-d x ) (ltd1 : infinite-d y ) → y ≡ x → ltd ≅ ltd1
|
|
156 lemma3 iφ iφ refl = HE.refl
|
|
157 lemma3 iφ (isuc {y} ltd1) eq = ⊥-elim ( ¬x<0 (subst₂ (λ j k → j o< k ) &iso eq (c<→o< (ω-∈s (* y)) )))
|
|
158 lemma3 (isuc {y} ltd) iφ eq = ⊥-elim ( ¬x<0 (subst₂ (λ j k → j o< k ) &iso (sym eq) (c<→o< (ω-∈s (* y)) )))
|
|
159 lemma3 (isuc {x} ltd) (isuc {y} ltd1) eq with lemma3 ltd ltd1 (ω-prev-eq (sym eq))
|
|
160 ... | t = HE.cong₂ (λ j k → isuc {j} k ) (HE.≡-to-≅ (ω-prev-eq eq)) t
|
|
161 lemma2 : {x y : Ordinal} → (ltd : infinite-d x ) (ltd1 : infinite-d y ) → y ≡ x → ω→nato ltd ≡ ω→nato ltd1
|
|
162 lemma2 {x} {y} ltd ltd1 eq = lemma6 eq (lemma3 {x} {y} ltd ltd1 eq) where
|
|
163 lemma6 : {x y : Ordinal} → {ltd : infinite-d x } {ltd1 : infinite-d y } → y ≡ x → ltd ≅ ltd1 → ω→nato ltd ≡ ω→nato ltd1
|
|
164 lemma6 refl HE.refl = refl
|
|
165 lemma : nat→ω (ω→nato ltd) ≡ * x₁
|
|
166 lemma = trans (cong (λ k → nat→ω k) (lemma2 {x₁} {_} ltd (subst (λ k → infinite-d k ) (sym &iso) ltd) &iso ) ) ( prev {* x₁} lemma0 lemma1 )
|
|
167
|
|
168 ω→nat-iso : {i : Nat} → ω→nat ( nat→ω i ) (ω∋nat→ω {i}) ≡ i
|
|
169 ω→nat-iso {i} = lemma i (ω∋nat→ω {i}) *iso where
|
|
170 lemma : {x : Ordinal } → ( i : Nat ) → (ltd : infinite-d x ) → * x ≡ nat→ω i → ω→nato ltd ≡ i
|
|
171 lemma {x} Zero iφ eq = refl
|
|
172 lemma {x} (Suc i) iφ eq = ⊥-elim ( ωs≠0 (nat→ω i) (trans (sym eq) o∅≡od∅ )) -- Union (nat→ω i , (nat→ω i , nat→ω i)) ≡ od∅
|
|
173 lemma Zero (isuc {x} ltd) eq = ⊥-elim ( ωs≠0 (* x) (subst (λ k → k ≡ od∅ ) *iso eq ))
|
|
174 lemma (Suc i) (isuc {x} ltd) eq = cong (λ k → Suc k ) (lemma i ltd (lemma1 eq) ) where -- * x ≡ nat→ω i
|
|
175 lemma1 : * (& (Union (* x , (* x , * x)))) ≡ Union (nat→ω i , (nat→ω i , nat→ω i)) → * x ≡ nat→ω i
|
|
176 lemma1 eq = subst (λ k → * x ≡ k ) *iso (cong (λ k → * k)
|
|
177 ( ω-prev-eq (subst (λ k → _ ≡ k ) &iso (cong (λ k → & k ) (sym
|
|
178 (subst (λ k → _ ≡ Union ( k , ( k , k ))) (sym *iso ) eq ))))))
|
|
179
|